2004
DOI: 10.1111/j.1600-0668.2004.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of indoor air temperature and humidity in an office on perceived air quality, SBS symptoms and performance

Abstract: The findings of this study indicate the importance of indoor air temperature and humidity on perceived air quality and SBS symptoms. In practice, the required ventilation rate for comfort and health should no longer be independent of indoor air temperature and humidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
160
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(191 citation statements)
references
References 7 publications
14
160
1
6
Order By: Relevance
“…Also, studies evaluating indoor environmental conditions in climate chambers and offices have shown that perception of air quality is significantly influenced by temperature and humidity (Fang et al, 2004). Wargocki (2004) agrees that the combined effect of olfactory, chemical and thermal sense affects the perception of air quality in the indoor environment.…”
Section: Introductionmentioning
confidence: 76%
“…Also, studies evaluating indoor environmental conditions in climate chambers and offices have shown that perception of air quality is significantly influenced by temperature and humidity (Fang et al, 2004). Wargocki (2004) agrees that the combined effect of olfactory, chemical and thermal sense affects the perception of air quality in the indoor environment.…”
Section: Introductionmentioning
confidence: 76%
“…There were many studies on a single aspect of the indoor environment, such as light or sound, but in the real world, these variables operate in concert. Studies have shown, for example, that as the temperature and humidity of indoor air increases, its perceived quality declines 6 . Programmes to reduce indoor air pollution could yield greater benefits if building managers pay attention to these other factors.…”
Section: Living In the Labmentioning
confidence: 99%
“…In this study experiments were conducted in controlled 'standard room conditions' based on guidelines contained in the, 21,22 at 23°C, 45% relative humidity and 0.08 m/s airflow.…”
Section: Controlled Environment Chambermentioning
confidence: 99%